Ecosystem functioning is linked to microbial evenness and community composition along depth gradient in a semiarid lake. (December 2021) - Zhang, Weizhen; Chen, Ruirui; Meng, Fanfan; Yuan, Haijun; Geng, Mengdie; Cheng, Longjuan; Yin, Huaqun; Xue, Bin; Wang, Jianjun
Graphical abstract: Highlights: Three microbial taxonomic groups show consistent water-depth distance-decay patterns. Ecosystem functions and multifunctionality generally increase towards deep water. Community composition and evenness dominate ecosystem multifunctionality variations. Water depth indirectly affects microbial diversity-ecosystem multifunctionality links. Abstract: Lake level or water depth are key physical variables known to respond dramatically to climate change, especially in arid regions, and their fluctuations exert substantial influences on lake biodiversity and ecosystem functioning. However, it is unclear how multiple ecosystem functions (i.e., ecosystem multifunctionality, EMF) respond to changes in water depth and how aquatic community attributes, such as species richness, evenness and community compositions, are linked to EMF along water depth gradients. Lake Hulun, a representative of semiarid-region lake in China, has experienced serious lake area shrinkage over the past 20 years. Here, we explored the water-depth patterns of three microbial taxonomic groups of bacteria, archaea and fungi and nine ecosystem functions related to nutrient cycling in Lake Hulun. We further examined the relative importance of different community attributes on EMF variations. We found that the community compositions of bacteria, archaea and fungi showed consistent water-depth decay patterns, and EMF and most individual ecosystem functions involved in C, N, P and S cycling increased with water depth. Further, EMF was predominantly mediated by microbial evenness and community composition, but not species richness, as predicted by the traditional theory of biodiversity-ecosystem functioning relationships. In addition, water depth indirectly affected the relationships between the microbial community and EMF via sediment nutrient contents. These findings indicate that the water depth changes under climate change could substantially alter ecosystem structure and functioning in arid regions. We further emphasize the necessity of including multiple community attributes in biodiversity-EMF relationship research to clarify the biotic and abiotic forces underlying EMF variations.